Anchoring nanoarchitectonics of 1T'-MoS2 nanoflakes on holey graphene sheets for lithium-ion batteries with outstanding high-rate performance. (20th January 2022) - Mi, Zhenjie; Hu, Danmei; Lin, Jingyi; Pan, Hui; Chen, Zhixin; Li, Yao; Liu, Qinglei; Zhu, Shenmin
Highlights: The 1T'-MoS2 nanoflakes were anchored on holey graphene (hG) sheets through a facile and scalable assembly approach. Energetically more favorable metallic 1T'-MoS2 was first used for LIBs anode, improving the overall conductivity. Abundant oxygenous groups on holey graphene facilitate the 2D/2D assembly with 1T'-MoS2 nanoflakes. Outstanding high-rate performance is obtained, with a capacity retention of 94.5% after 2000 cycles at 5 A g −1 . Abstract: Rapid charging is of high demand in lithium-ion batteries (LIBs). Molybdenum sulfide (MoS2 ) has attracted great interest as a potential anode for LIBs due to its high theoretical capacity. However, low electronic conductivity and severe volume change upon lithiation/delithiation hinder its applications, especially in high-rate applications. Herein, we develop a facile assembly process to fabricate a highly conductive 1T'-MoS2 /rhGO composite where rhGO is referred as reduced holey graphene oxide. The abundant oxygen-containing groups on holey graphene make it possible for realizing 2D/2D assembly of 1T'-MoS2 with graphene oxide. When used in LIBs, the 1T'-MoS2 /rhGO anode delivered a high specific capacity of 1084 mAh g −1 at 0.2 A g −1 and outstanding high-rate performance, 635 mAh g −1 at a large current density of 5 A g −1 for 2000 cycles with capacity retention reaching 94.5%. The excellent high-rate performance is attributed to the synergic effects of the metallic 1T'-MoS2 and the holey graphene matrix. The former increases the overall conductivity while the latter anchors 1T'-MoS2 nanoflakes tightly through chemical bonding, thus preventing volume changes during cycling. This facile approach for achieving 2D and 2D assembly paves a new way of developing high-rate performance anodes for LIBs which can better fulfill the demand for fast-charging technology.